High-dose Versus Low-dose Tranexamic Acid to Reduce Transfusion Requirements in Pediatric Scoliosis Surgery. Issue 8 (December 2017) - Johnson, Daniel J.; Johnson, Christine C.; Goobie, Susan M.; Nami, Nina; Wetzler, Joshua A.; Sponseller, Paul D.; Frank, Steven M.
Abstract : Background: Our objective was to quantify blood loss and transfusion requirements for high-dose and low-dose tranexamic acid (TXA) dosing regimens in pediatric patients undergoing spinal fusion for correction of idiopathic scoliosis. Previous investigators have established the efficacy of TXA in pediatric scoliosis surgery; however, the dosing regimens vary widely and the optimal dose has not been established. Methods: We retrospectively analyzed electronic medical records for 116 patients who underwent spinal fusion surgery for idiopathic scoliosis by a single surgeon and were treated with TXA. In total, 72 patients received a 10 mg/kg loading dose with a 1 mg/kg/h maintenance dose (low-dose) and 44 patients received 50 mg/kg loading dose with a 5 mg/kg/h maintenance dose (high-dose). Estimated blood loss and transfusion requirements were compared between dosing groups. Results: Patient characteristics were nearly identical between the 2 groups. Compared with the low-dose TXA group, the high-dose TXA group had decreased estimated blood loss (695 vs. 968 mL, P =0.01), and a decrease in both intraoperative (0.3 vs. 0.9 units, P =0.01) and whole hospitalization (0.4 vs. 1.0 units, P =0.04) red blood cell transfusion requirements. The higher-dose TXA was associated with decreased intraoperative ( P =0.01), and whole hospital transfusion ( P =0.01) requirements, even after risk-adjustment for potential confounding variables. Conclusions: High-dose TXA is more effective than low-dose TXA in reducing blood loss and transfusion requirements in pediatric idiopathic scoliosis patients undergoing surgery. Level of Evidence: Level—III, retrospective cohort study.